Communicative Language Teaching in the Moroccan Classroom: Perception, Practices, and Difficulties - Diouani, Azz-Eddine (Journal of Foreign Language Teaching and Learning, 2020)
Research on the teaching practices of EFL teachers has revealed that teachers' beliefs are often at odds with their actual classroom practices. Accordingly, the present investigation compared teachers' perceptions and classroom practices of the Communicative Language Teaching principles (CLT) in the provincial directorate of Jerada. This exploration is an attempt to examine teachers' practices, thereby draw a line between what they think they do and what they do in the classroom. To this end, ten teachers were interviewed. Out of this number, only two teachers were observed. The data gathered via semi-structured interviews have shown that the teacher respondents were well-informed about the principles of Communicative Language Teaching (CLT). However, the data collected by the classroom observations revealed that the teachers were not teaching English communicatively. Factors such as learner's language proficiency, lack of knowledge as to how to implement the approach, unsuitable textbooks, and lack of motivation on the part of the learner, contributed enormously to the non-use of the CLT. To overcome these obstacles, the findings of the current study suggest that EFL teachers "should" motivate students, use simple fluency-oriented tasks, simplify, model, and scaffold the learning activities. They also recommend to adapt the textbooks to students' needs, research their practice, and invest more in their professional development. The Ministry of National Education is required to provide high-quality training to help teachers cope with the demands of the Communicative Approach.